(untitled) (Jurnal Adabiya, 2020)
Al-Qur’an copying has been carried out by various walks of life from various sides since the centuries. This article examines ancient manuscripts from historical aspects, to see the potential and prospects of the study of the ancient manuscripts, by collecting literature studies, interviews, and observations or direct observation is carried out to see and examine how the manuscript is treated. From the results of this ancient manuscript research, it can be seen the development of the writing and copying of the Koran in various forms, variety and appearance, various beautiful illuminations that have peculiarities, and their own uniqueness. Even the writing text uses different calligraphy between one manuscript and another. With this research can provide more extensive learning about ancient manuscripts, so that this manuscript is not only seen as a holy book in terms of religion, but also education, especially education related to manuscripts from the codicological and philological aspects.